Oxidative Stress Is Associated with Neuroinflammation in Animal Models of HIV-1 Tat Neurotoxicity - Jean-Pierre Louboutin; Lokesh Agrawal; Beverly A. S. Reyes; Elisabeth J. Van Bockstaele; David S. Strayer (MDPI AG, 2014)
HIV-1 trans-acting protein Tat, an essential protein for viral replication, is a key mediator of neurotoxicity. If Tat oxidant injury and neurotoxicity have been described, consequent neuroinflammation is less understood. Rat caudate-putamens (CPs) were challenged with Tat, with or without prior rSV40-delivered superoxide dismutase or glutathione peroxidase. Tat injection caused oxidative stress. Administration of Tat in the CP induced an increase in numbers of Iba-1- and CD68-positive cells, as well as an infiltration of astrocytes. We also tested the effect of more protracted Tat exposure on neuroinflammation using an experimental model of chronic Tat exposure. SV(Tat): a recombinant SV40-derived gene transfer vector was inoculated into the rat CP, leading to chronic expression of Tat, oxidative stress, and ongoing apoptosis, mainly located in neurons. Intra-CP SV(Tat) injection induced an increase in microglia and astrocytes, suggesting that protracted Tat production increased neuroinflammation. SV(SOD1) or SV(GPx1) significantly reduced neuroinflammation following Tat administration into the CP. Thus, Tat-induced oxidative stress, CNS injury, neuron loss and inflammation may be mitigated by antioxidant gene delivery.